Impact of lime on compaction characteristics of Jamshoro shale - Shoaib Abdullah,; Nouman Ali,; Muhammad Behram,; Aneel Kumar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The most complex problem for any civil engineering work is when the structure which is laying on the soil is weak. Jamshoro shale is an example of such problematic soil, which gets expanded as soon as it is exposed to moisture and shrinks back once it dries. Such phenomenon is very critical for the structures and road networks built on shale forming settlements and cracks. Such kinds of soil must be stabilized by chemical or mechanical techniques to make them strong enough to carry the loads and resist settlements and cracking. The stabilization of the ground by utilizing or adding any chemical agent is a sustainable approach; it strengthens the soil properties without replacing or wasting the soil present. In this research, the treatment of lime with shale is been performed to observe the modification of the geotechnical characteristics of the soil. The different proportions of Hydrated Lime 0%, 7%, 8%, and 9% were mixed by the dry weight of soil to investigate the effect of lime on the compaction and plasticity characteristics of the shale. Various tests such as the modified proctor test, liquid limit test, and plastic limit test performed in the laboratory. From the results, it was observed that the properties of Jamshoro shale such as plasticity index, optimum moisture content, and maximum dry density were improved. The plasticity index of shale dropped to 2% from 24%. That suggests lime can be used as an economical and eco-friendly stabilizing agent.